AN ANALYSIS OF CULTURAL CONTENTS OF AN ENGLISH TEXTBOOK FOR ELEMENTARY SCHOOL - Risna Ariana, - (2019)
This paper reports on the study that analyzed the cultural contents represented in an English textbook for elementary school. The data were collected from the English textbook for elementary school entitled Grow with English for third grade published by Penerbit Erlangga. The study used two major frameworks: (1) types of culture; the source culture, the target culture, and the international culture proposed by Cortazzi & Jin (1999), and (2) the four senses of culture; the aesthetic sense, the sociological sense, and semantic sense, and the pragmatic sense proposed by Adaskou, Britten & Fahsi (1990). This research was descriptive qualitative study focusing on the content analysis. The research findings indicated that the source culture is predominantly embodied in the textbook. This is considered as the purpose of the authors to include diverse local contexts since the textbook was written by local authors and produced by a local publisher. In terms of sense of culture, the sociological sense is mainly represented in the textbook compared to another sense. This is because the aspects of the sociological sense are categorized as the ways of life. Integrating the types of cultures and the four senses of culture, the findings were significantly dissimilar. The source culture is mostly represented through the sociological sense because most of the themes of the lessons related to the ways of source culture life. Then the target culture is mostly represented by the pragmatic sense since all language forms and functions are in the English language. Finally, except the pragmatic sense, the international culture is represented by the same average of the aesthetic sense, the sociological sense, and the semantic sense.